Peran Posyandu Sebagai Pelayanan Dasar Kesehatan dan Pemberdayaan Masyarakat di Desa Jaya Asri: Peran Posyandu Sebagai Pelayanan Dasar Kesehatan dan Pemberdayaan Masyarakat di Desa Jaya Asri - Yuyun Fitriani; Sigit Setioko; Mirnawati Mirnawati; Maulana Yusuf; Henny Widya Putri; Asih Setiani; Elva Delvina; Lawrenta Catrina (Institut Riset dan Publikasi Indonesia (IRPI), 2023)
Posyandu is a center for basic health services for mothers and children under five. Posyandu is a form of community empowerment in villages. Community empowerment is all facilitation efforts that are non-instructive in nature, in order to increase the knowledge and abilities of the community, so that they are able to identify the problems they face, their potential, plan and carry out solutions by utilizing local potential. Community empowerment in the health sector is the process of providing information to individuals, families or groups (clients) continuously and continuously following the client's development, as well as the process of helping clients, so that the client changes from not knowing to knowing or being aware (aspect of knowledge), from knowing to wanting (attitude aspect), and from wanting to being able to carry out the behavior being introduced (action or practice aspect). The results of service activities show that the role of posyandu as a basic health service and community empowerment in Jaya Asri Village has been running well. This can be seen by the education of posyandu cadres and mothers of toddlers so that the stunting rate in Jaya Asri village is low. The village government also provides support by providing good facilities and infrastructure. So that posyandu cadres are able to be empowered and manage their organization well.